Métricas de Logística y su relación con la Rentabilidad en la empresa distribuidora Venus del Oriente E.L.R.L 2009-2013 Rioja - García Ramírez, Alex Fernando (2015)
The research comes as the main objetivo determine the relationship between logistics metrics and profitability through document analysis technique to collect financial information from the distributor VENUS OF ORIENT E.l.R.L in the period 2009 - 2013, Rioja. Far which is based on a population of five years for the study. Reached the fallowing conclusions: Metrics logistics company Distribuidor Venus of Orient E.I.R.L is poor because from the period 2009 to 2013 the rejected and returned orders generated an imbalance in total orders for the company. And also the sale is thus affected, because the distributor could not ask for further pairs of shoes by the problem of poor logistics process control. The profitability of the company Distribuidor Venus of Orient E.l.R.L varaciones suffers constant as compared with gross and net income, because the costs for the distribution of footwear are not issuing satisfactorily and therefore this directly affecting the profitability of the company. Therefare it is concluded that the profitability of the company and found wanting very changeable The relationship between logistics metrics and profitability of Distribuidor Venus of Orient E.l.R.L is existing because through constrastacion the null hypothesis Ho is rejected and H1 hypothesis was accepted. Therefore it is concluded that the correlation between the two variables objects of study for Distribuidor Venus of Orient E.l.R.L